Bistable Color‐Tunable Liquid Crystal Fiber by the Method of Mechanical Drawing with Synchronous Ultraviolet Polymerization. Issue 11 (25th August 2021) - Wang, Yingli; Zhang, Mengxue; He, Xiaoxian; Zhang, Wenzhao; Wu, Shuanghong; Huang, Xiaoping; Yu, He; Wang, Xiangru
Abstract: A color‐tunable fiber is demonstrated to reflect colors by switching the electric field on a chiral liquid crystal (CLC) with different helical twisting powers. With the purpose of bistability and low power consumption, the mechanism of the CLC fiber proposed in this study is an electric‐field‐induced phase change. To maintain the balance of wearable flexibility and mechanical stability, the liquid crystal fiber is constructed by the method of mechanical drawing with synchronous ultraviolet polymerization. To be a typical 1D structure, the central core of the CLC fiber is made of an aluminum wire, which is used to load the driving voltage as well as a mechanical support. In addition, there are three claddings surrounding the central core: the color‐tunable cladding filling with CLC material, the polymer cladding to anchor the liquid crystal, and the outer transparent electrode cladding. Bistable color change is realized by switching two given voltages corresponding to the planar state (P‐state) and focal conic state (FC‐state). Furthermore, to knit N fibers together, 2 N colors can be realized by applying electric voltages to the fiber bundle. Abstract : By the method of mechanical drawing with synchronous ultraviolet polymerization, a color‐tunable fiber with three claddings is demonstrated to reflect colors by switching the electric field on a chiral liquid crystal with different helical twisting powers. Furthermore, to knit N fibers together, 2 N colors can be realized by applying electric voltages to the fiber bundle.